Experimental Study on Water Filtration System by Using Clay-Kenaf-Biochar for Agriculture Uses - Ku Mahmood, Ku Muhammad Iskandar; Mohid, Zazuli; Kamdani, Kamaruddin (Research Progress in Mechanical and Manufacturing Engineering, 2024)
In this study, researchers developed a water filtration system for reducing heavy metals and anions in Malaysian water sources using Clay, Kenaf, and Biochar in optimal ratios. The study successfully produced effective filter bricks, emphasizing the potential of natural resources for sustainable water treatment. CKB’s brick demonstrated superior effectiveness in reducing heavy metal content. However, limitations included excluding other potential materials, small-scale testing, and limited water sample locations around Parit Raja. Despite these, the study contributes to eco-friendly water treatment, prompting future research. The research focused on mixing ratios and filter element evaluation, highlighting effective heavy metal reduction but inefficiencies for anions and mercury. Recommended improvements include expanding mixing ratio experimentation, individualized material studies, and increased water sample locations for a comprehensive assessment. These suggestions aim to fortify the knowledge foundation and contribute to more effective and adaptable water treatment solutions.